Transfer free graphene growth on SiO2 substrate at 250 C - Vishwakarma Riteshkumar, Rosmi Mohamad Saufi, Takahashi Kazunari, Wakamatsu Yuji, Yaakob Yazid, Ibrahim Araby Mona, Kalita, Golap, Kitazawa Masashi, T (Researchgate, 2017)
Transfer free graphene growth on SiO2 substrate at 250 C by Vishwakarma Riteshkumar, Rosmi Mohamad Saufi, Takahashi Kazunari, Wakamatsu Yuji, Yaakob Yazid, Ibrahim Araby Mona, Kalita, Golap, Kitazawa Masashi, T